MULTICULTURALISM & DEMOCRACY EDUCATION IN POLITICAL AND CULTURAL BASED CONFLICT RESOLUTION PROCESS IN EAST KALIMANTAN - Suwoko Suwoko (Universitas Muhammadiyah Surakarta, 2022)
Indonesia is an archipelago country with differences in ethnicity, race, religion, and between groups. Pancasila is a key that can unite. In line with the life of the Indonesian people, horizontal conflicts are very prone to occur in Indonesia, which can cause friction between ethnicities, races, ethnicities, religions, and groups. Horizontal conflicts often occur due to several factors, including deep-rooted economic, social, and cultural factors. Based on the history of the Indonesian nation towards this horizontal conflict, it is necessary to resolve and resolve the conflict with a political and cultural approach that can dilute the heated situation. The importance of Multiculturalism Education for the Indonesian people can be a way out and a way of life for the Indonesian people by utilizing culture as a bridge and politics as a forum for reaching consensus on a problem in horizontal conflict. The method used is a qualitative method with Multiculturalism Democracy Education in the Process of Conflict Resolution Based on Politics and Culture in East Kalimantan. The data collection technique was carried out using a literature study so that the data used came from journals and government laws that were correlated with the context of the issues discussed in this article. In the application of multiculturalism, in theory, the people of East Kalimantan are very understanding. In line with its application with clear evidence, one of which is the establishment of inter-regional forums, group discussion forums, and inter-cultural events where indirectly the community has vital harmony and coexistence without any sense of difference that can cause conflict. multiculturalism as an Approach and as a National Policy As stated above, multiculturalism is an ideological solution to the problem of the decline in the power of integration and nationalism awareness of a nation as a result of changes at the global level.